EVALUATING HEALTH-RELATED QUALITY OF LIFE IN PATIENTS WITH YOUNG-ONSET TYPE 2 DIABETES IN SINGAPORE USING EuroQol EQ-5D-5L - Goh, Li Xian; Ting, Wan; Chan, Lovynn; Ang, Su Fen; Chian, Winston Kon Yin; Vasanwala, Rashida Farhad; Loh, Wann Jia; Lim, Su Chi (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Despite multiple efforts to create awareness and reduce the rise of young-onset T2D (YT2D), the prevalence of YT2D remains high in Singapore. There is also limited information on how YT2D patients have been coping with their chronic condition. We hypothesize that YT2D patients face a myriad of challenges in their daily routine and aim to determine specific areas to focus on for providing patient-centred care. METHODOLOGY The 269 patients (onset age ≤35 years) enrolled were subjected to the EQ-5D-5L questionnaire upon recruitment. EQ-5D-5L consists of a descriptive page, which comprises 5 dimensions: mobility, self-care, usual activities, pain/ discomfort, anxiety/depression with 5 response levels, and an EQ-VAS scale (0-100), which evaluates health status and health preference. Health states were validated against the Singapore valuation set. RESULTS Majority (72.1%) of the patients (mean ± SD age: 33.7 ± 13.8, diabetes duration: 10.5 ± 10.6) reported a full health state of “11111”. Of the remaining patients, 15.2% and 14.9% reported problems of varying severity under pain/ discomfort and anxiety/depression, respectively. Mean VAS score was 79.3 (range 30-100) with 29% reporting a score of ≤70. A longer duration of diabetes was found to be associated with lower VAS scores (≤70 or >70) (OR=1.04, 95% CI: 1.01-1.09, p=0.028) after adjusting for age, gender, ethnicity, BMI and HbA1c. CONCLUSION Our results suggest that patients with younger-onset and longer diabetes duration have lower self-rated quality of life. We identified pain/discomfort and anxiety/depression as two areas of concern that clinical care providers can focus on to better support patients in their diabetes care.